EDUKASI TEKNOLOGI LADA PERDU BAGI FORUM PEMUDA DI KECAMATAN MARUSU KABUPATEN MAROS - Netty Syam; Hidrawati Hidrawati; A. Ralle (Lembaga Pengabdian kepada Masyarakat Universitas Muslim Indonesia, 2026)
The allocation of leisure time among youth can be optimized through engagement in productive and educational activities, including the cultivation of plants in underutilized yard areas. This Community Service (CS) initiative is intended to strengthen the partners’ competencies and technical skills in cultivating pepper bushes, thereby promoting the strategic utilization of yard spaces for productive, effective, and efficient land-use practices. The specific target to be achieved is the utilization of yard land that has been left empty and unmanaged, by planting Pepper Bushes. Partners are members of the Pattene Creative Youth Communication Forum (Forkompak) youth group, most of whom live in Pattene hamlet, Temmappaduae Village, Maros. The method used in PKM is providing Training, Mentoring, and Plot Demonstration to Partners. The partners who will be involved are 10 (ten) Forkompak members and will be given 10 (ten) Pepper Bush seeds each to plant in their yard. The results of this PKM activity are expected to (1) improve Partners' skills in cultivating Pepper Bushes and (2) grow Pepper Bushes in the yards of each Partner group member. The results of this activity will also be published in online media and the Balireso journal.